THE APRIL 2007 SWARM IN TRICHONIS LAKE USING DATA FROM A MICROSEISMIC NETWORK - Sokos, E.; Pikoulis, V.E.; Psarakis, E.Z.; Lois, A. (Bulletin of the Geological Society of Greece, 2010)
A series of strong earthquakes took place at the Trichonis lake area, during April 2007. Three events, with M~5.0 occurred within one day, causing damages to almost all nearby villages and especially at the small town of Thermo. The sequence lasted for more than one month with small to moderate size events. It was recorded by regional networks and results related to its time and space evolution have already been published. Just after the major events a microseismic network was deployed in the area, by the University of Patras, Seismology Laboratory. Eight stations were installed, with short period, three component sensors and portable digital recorders. The network was in operation for a period of one month and a lot of events were recorded by enough stations to provide a reliable location. We present here the analysis of these data using modern methodologies like waveform cross-correlation techniques and further relocation of the events using waveform based differential time. The results partially support the findings of the regional networks, as regards the gross characteristics of the aftershock sequence, but provide an enhanced description of it. The space time evolution of the aftershock sequence reveals the activation of more than one fault in the area and suggests the connection of the sequence with an unmapped fault.